Impact of Land Degradation on Irish Potato Production in Hamurwa Sub-County Rubanda District. - Ahimbisibwe, Columbus (Kabale University, 2024)
This study focused on the impact of land degradation on Irish potato production in the Hamurwa Sub-county Rubanda district. The objectives of the study were; to determine the main causes of land degradation in Irish potato production in Hamurwa Sub- County Rubanda district, to identify the most common and disastrous forms of land degradation in Hamurwa Sub-County Rubanda district, and to determine how land degradation has impacted on agricultural productivity of Irish potatoes in Hamurwa Sub- County Rubanda district. A descriptive research design was employed and data collection tools included questionnaires and an interview guide which were used to collect data from 50 respondents mainly farmers from the Hamurwa sub-county, leaders, and community members. Descriptive statistics using Microsoft Excel and SPSS were used and the findings were presented in tables, charts, and graphs. The study finding indicates that there were land use practices such as mono-cropping, deforestation, overgrazing, and settlements, which have affected Irish potato production. The findings of the study indicate that there were effects of land use practices on Irish potato production as they include; low-quality yields, decreased Quantity yield or yield per acre, and improved food security, the study recommends that there is a need for farmers to apply natural manures in order to get high quality and quantity yields and increase on food production. The use of farmyard manure should be encouraged to restore land cover. This should be done along with good husbandry practices such as crop rotation, and rotational grazing to avoid exhausting a particular plot of land in a short period, which in most cases forces people to exhaust land, there is a need for policymaking concerning land use through a forestation thus discouraging or reducing deforestation and there should education of masses should be encouraged relating to the efficient use of land use practices on Irish potato production through sensitizing people on dangers of destroying agricultural and its related effects.